Thermal conductivity and compressive strength of carbon fiber concrete (Journal of Architectural Design, 2022)
This research includes an experimental study to find out the possibility of benefiting from the addition of Carbon Fiber Reinforced Polymers (CFRP) to the concrete mix in reducing the thermal conductivity of concrete and thereby reducing the heat transferred through the structures and elements of buildings, which leads to increased thermal insulation and reduce the electrical energy consumed to operate air conditioners. Eight rectangular concrete specimens are prepared and poured for thermal conductivity testing, in addition to 12 standard concrete cubes for compressive strength testing. CFRP strips cut in different proportions are added to find out the effect of the amount of these fibers on the thermal insulation of concrete and compare it with their effect on compression resistance. The results of the thermal conductivity tests for a test time of 390 minutes for each model showed that there is an increase in the insulation of concrete with added percentage of CFRP strips. The concrete specimens and cubes are classified into four groups according to the percentage of addition of CFRP, which was (0 %, 0.45 %, 1.1 %, and 1.6 %) by the weight of the cement allocated for the mixture. Despite the increase in insulation with the presence of fibers, there was a decrease in the compressive strength of concrete with an increase in the amount of fibers, where this decrease ranged between (6.4 - 28.5) % relative to the compressive strength of the reference concrete